2001
DOI: 10.1046/j.1432-1327.2001.02099.x
|View full text |Cite
|
Sign up to set email alerts
|

Defects of type I procollagen metabolism correlated with decrease of prolidase activity in a case of lethal osteogenesis imperfecta

Abstract: We have studied the structure and metabolism of type I procollagen in a case of perinatal lethal osteogenesis imperfecta (OI) type II. Cultured skin fibroblasts from the proband synthesized both normal and abnormal forms of type I procollagen. Some abnormal, overmodified molecules were secreted by OI cells, although less efficiently than normal molecules from control cells. The OI fibroblasts accumulated large amounts of abnormal proa1(I) and proa2(I) chains intracellularly. The extracellular collagenolytic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…In our opinion this view is short-sighted since by researching this disease the opportunity increases to unlock the mystery of cell metabolism. For instance, in a series of interesting papers published by Palka et al, the levels of prolidase activity have been shown to correlate with collagen synthesis in Osteogenesis imperfecta [52,53], in pancreatic diseases [54] or in lung carcinoma planoepitheliale [55] and breast cancer MCF-7 cells [56][57][58]. These and other papers clearly indicate how important is the role of prolidase in collagen metabolism.…”
Section: Discussionmentioning
confidence: 96%
“…In our opinion this view is short-sighted since by researching this disease the opportunity increases to unlock the mystery of cell metabolism. For instance, in a series of interesting papers published by Palka et al, the levels of prolidase activity have been shown to correlate with collagen synthesis in Osteogenesis imperfecta [52,53], in pancreatic diseases [54] or in lung carcinoma planoepitheliale [55] and breast cancer MCF-7 cells [56][57][58]. These and other papers clearly indicate how important is the role of prolidase in collagen metabolism.…”
Section: Discussionmentioning
confidence: 96%
“…Compound [7] was a less effective stimulator since it increased collagen synthesis by 63% of the control. It is known that disturbances in proline and lysine hydroxylation as well as lysine glycosylation of procollagen chains result in retarded folding and secretion, and consequently in increased intracellular degradation of procollagen (2,3,27,28). Secretion of procollagen into media by the compound-treated cells was normal or slightly increased which suggests that they did not affect either modification or folding of procollagen chains.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies showed that there is a relationship between serum prolidase concentrations and bone metabolism [4,7,10,13,14]. Verit et al [4] showed that serum levels of prolidase were significantly elevated in postmenopausal osteoporotic women compared with premenopausal women; however, there was no correlation between serum prolidase levels and bone turnover markers in the postmenopausal osteoporotic group.…”
Section: Discussionmentioning
confidence: 99%
“…This recycling is important for collagen resynthesis and cell growth [10,11]. Prolidase enzyme activity has been investigated in the context of various disorders such as coronary artery disease [12], osteoporosis [4,7], osteoarthritis [10], uremic bone disease [13], and osteogenesis imperfecta [14]. These disorders have showed a relationship between serum prolidase concentrations and disease activity and/or bone metabolism.…”
Section: Introductionmentioning
confidence: 99%